The Effectiveness of Family Mediation in Domestic Violence Cases from an Islamic Perspective: Between Peaceful Resolution and Victim Protection: A Legal and Religious Analysis of Conflict Resolution Mechanisms in Domestic Violence within Muslim Families - Pramudita Paramadewi Hariyanto; Farid Wajdi; Lucky Dafira (SAMAWA, 2025)
Domestic violence (DV) is a multidimensional issue that encompasses legal, social, and cultural aspects. Although regulations such as Law Number 23 of 2004 on the Elimination of Domestic Violence have been enacted, in reality, the implementation and protection for victims remain weak. Many DV cases are resolved informally due to strong social norms and patriarchal cultural values, especially in certain regions of Indonesia. This article examines the effectiveness of family mediation approaches from an Islamic perspective as an alternative resolution for domestic violence. In Islam, mediation or tahkim is viewed as a peaceful solution grounded in the values of justice, compassion, and victim protection. Through a normative juridical approach and qualitative analysis, this article highlights that Islamic mediation can serve as a resolution instrument that not only reconciles but also ensures the safety and rights of victims—provided it is conducted by competent mediators who understand victim protection principles. Therefore, synergy between Islamic law and positive law is essential to achieving justice and preventing recurring violence within families.